SANKSI ADMINISTRATIF SEBAGAI SALAH SATU INSTRUMEN PENEGAKAN HUKUM DALAM PERATURAN PERUNDANG-UNDANGAN - Setiadi, Wicipto (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Implementation of legislation would be ineffective if not accompanied bylaw enforcement. Law enforcement against legislation to many differentforms, one of whom formulated in terms of sanctions, which may includecriminal sanctions, civil penalties or administrative sanctions. The provisionsof this sanction, whether criminal, civil, or administrative is an option,meaning no need to apply all three but it can be chosen which are the mosteffective and most appropriate that the scope associated with the substanceof regulation. In fact, it is possible from a law enforcement legislation wasnot needed any sanctions. Inclusion of sanctions should also be adjusted tothe substance set forth in laws and regulations are. For the substance ofissues related to administrative, administrative sanctions are most effective.Administrative sanctions can be applied either through the courts or throughnon-court line, i.e. by administration officials. Administrative sanctions setforth in the legislation most relevant to the licensing issues and implementedby the authorities (bodies) administration authorized to issue such permits.Administrative sanctions imposed by administrative authorities are oftenrelated with violations of licensing requirements. An administrative sentenceneeds a legal basis with the possibility for the sentences person the havea legal effort to sue the administrative sanction.